ABSORPTION OF SHORT-PERIOD TRANSVERSE WAVES IN THE LITHOSPHERE AND ASTHENOSPHERE UNDER CRATONS AND SEMICRATONS - Kopnichev Yu.F. (My University, 1989)
We have earlier developed methods of investigating the absorption field in the crust and upper mantle based on an analysis of the characteristics of irregular seismic waves, i.e., codas, at distances of up to 2000 to 2500 km. These methods rely on analysis of the characteristics of short-period transverse waves, which are very sensitive to the presence of partially molten material in the medium through which they propagate. This makes it possible to extract certain important structural details of the crust and upper mantle, which apparently would be difficult or impossible to detect by analyzing longitudinal wave velocities or absorption. In the present paper we use these methods to analyze the structure of the lithosphere and asthenosphere under cratonic and the younger, semicratonic regions of Eurasia. Our data indicate that the structure of the upper mantle differs considerably in regions of cratons and of younger regions such as semicratons. The main difference is apparently that a relatively thin layer of anomalous mantle is present under the semicratons, and that this layer is either absent or very marginal under semicratons.